Integrasi Sistem Penjaminan Mutu Eksternal Dan Internal Berbasis Internet dalam Meningkatkan Akuntabilitas Pendidikan di Era Digital - Widya Isma Dayanti; Syafitri Aulia Wulandari; Siti Maryamah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Educational institutions are under pressure to create organized and responsible quality assurance systems because raising the standard of education has become a global imperative. The Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME) are integrated in Indonesia to achieve this. However, accountability must be transparent, real-time, and not just administrative due to the quick digital revolution. In order to enhance educational accountability in the digital age, this study attempts to examine and model the integration of internet-based internal and external quality assurance systems. Nine pertinent papers from 2018 to 2025 were chosen and examined using a systematic Literature Review (LR) process and a qualitative methodology. The findings show that institutional performance and accountability are greatly improved by the successful implementation of SPMI, which is driven by the PPEPP cycle (Planning, Implementation, Evaluation, Control, and Improvement). Additionally, the integration of digital-based systems (e-SPMI) acts as a link between SPME and SPMI, guaranteeing data correctness, efficiency, and transparency for accrediting needs. The results highlight the need for an integrated, web-based quality assurance system that facilitates evidence-based decision-making in order to attain educational accountability in the digital age. In order to automate data collection and reporting procedures, the study advises educational institutions to implement an online quality management information system